Intraoperative Contrast-Enhanced Ultrasound for Brain Tumor Surgery. Issue 5 (6th March 2014) - Prada, Francesco; Perin, Alessandro; Martegani, Alberto; Aiani, Luca; Solbiati, Luigi; Lamperti, Massimo; Casali, Cecilia; Legnani, Federico; Mattei, Luca; Saladino, Andrea; Saini, Marco; DiMeco, Francesco
Abstract: BACKGROUND: Contrast-enhanced ultrasound (CEUS) is a dynamic and continuous modality that offers a real-time, direct view of vascularization patterns and tissue resistance for many organs. Thanks to newer ultrasound contrast agents, CEUS has become a well-established, live-imaging technique in many contexts, but it has never been used extensively for brain imaging. The use of intraoperative CEUS (iCEUS) imaging in neurosurgery is limited. OBJECTIVE: To provide the first dynamic and continuous iCEUS evaluation of a variety of brain lesions. METHODS: We evaluated 71 patients undergoing iCEUS imaging in an off-label setting while being operated on for different brain lesions; iCEUS imaging was obtained before resecting each lesion, after intravenous injection of ultrasound contrast agent. A semiquantitative, offline interobserver analysis was performed to visualize each brain lesion and to characterize its perfusion features, correlated with histopathology. RESULTS: In all cases, the brain lesion was visualized intraoperatively with iCEUS. The afferent and efferent blood vessels were identified, allowing evaluation of the time and features of the arterial and venous phases and facilitating the surgical strategy. iCEUS also proved to be useful in highlighting the lesion compared with standard B-mode imaging and showing its perfusion patterns. No adverse effects were observed. CONCLUSION: Our study is the first large-scale implementation of iCEUS in neurosurgery as a dynamic and continuous real-time imaging tool for brain surgery and provides the first iCEUS characterization of different brain neoplasms. The ability of CEUS to highlight and characterize brain tumor will possibly provide the neurosurgeon with important information anytime during a surgical procedure.